Larval settlement and metamorphosis of the invasive biofouler, Mytilopsis sallei, in response to ions and neuroactive compounds. Issue 6 (3rd July 2017) - He, Jian; Qi, Jian Fei; Huang, Yan Qiu; Sheng, Yan Qing; Su, Pei; Feng, Dan Qing; Ke, Cai Huan
ABSTRACT: In this study, we investigated larval settlement and metamorphosis of the invasive fouler Mytilopsis sallei exposed to ions, neurotransmitters and blockers inhibiting their respective actions. Excess K + effectively induced larval settlement and metamorphosis, while the voltage-gated potassium channel blocker, TEA, significantly inhibited the K + inducing effect, suggesting that a voltage-gated potassium channel may play a role in M. sallei settlement and metamorphosis. Excess Ca 2+ did not induce larval settlement and metamorphosis, while Mg 2+ and inhibited both. Among the neurotransmitters, GABA did not induce M. sallei larvae to settle and metamorphose at 10 −6 –10 −4  M concentrations, while 5 × 10 −5 –10 −4  Ml -DOPA (a dopamine precursor), 5 × 10 −6 –10 −4  M dopamine (an epinephrine precursor) and 5 × 10 −5 –10 −4  M epinephrine significantly induced larval settlement and metamorphosis, indicating the presence of an epinephrine biosynthesis pathway in this species and its role in the regulation of larval settlement and metamorphosis. Furthermore, the inducing effect of dopamine on M. sallei settlement and metamorphosis was inhibited by SCH23390, a selective D1 dopamine receptor antagonist. Similarly, the inducing effect of epinephrine was inhibited by chlorpromazine, an α 1 -adrenergic antagonist, suggesting that the D1 dopamine receptor and α 1 -adrenoceptor may play active roles in the processes of settlement and metamorphosis of M. sallei larvae. Here, we have shown for the first time the responses of larval settlement and metamorphosis of dreissenid mussels to pharmacologically active compounds. The results provide new insights into the biochemical mechanisms underlying larval settlement and metamorphosis of M. sallei, which may be useful to develop effective strategies to control this invasive fouling organism.